STRATEGI PEMASARAN KOMPETITIF DALAM MENGHADAPI PERSAINGAN INDUSTRI BISNIS DI INDONESIA - Abdullah, Abdullah; Yoniton, Wini Kartini; Karunia, R. Luki; Nugroho, Michael Adhi (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to analyze the digital innovation-based competitive marketing strategy implemented by PT Amara Tujuh Perjuangan in facing competition within Indonesia’s exhibition industry. Using a qualitative approach with a descriptive case study design, the research focuses on the application of the Business Model Canvas (BMC) and digital transformation strategy as the main frameworks for understanding modern marketing dynamics. Data were collected through in-depth interviews, observations, and documentation involving company management, marketing staff, and key customers. The findings indicate that the integration of BMC with digital innovation strengthens the company’s competitive advantage by enhancing operational efficiency, personalizing services, and improving customer relationships. The digital platform Auto360 plays a crucial role in expanding market reach, optimizing promotional costs, and increasing customer engagement. However, challenges remain in digital literacy and customer analytics integration. Conceptually, this study emphasizes the importance of synergy between technological innovation, customer orientation, and internal resource management in creating adaptive and sustainable marketing strategies in the era of industrial digitalization.